Students’ Mathematical Beliefs At School That Separate Gender Based On Students’ Mathematical Autobiography - Fitri Kumala Dewi; Tati Wulandari; Meirisa Sahanata (Sustainability (STPP) Theory, Practice and Policy, 2022)
This study aims to know the change in mathematical beliefs of students grade VII from elementary school until now in Junior High School through students’ mathematical autobiography. The research design used in this study is qualitative descriptive. The data were obtained by using questionnaires and interviews. Instruments in this study are researchers as the main instrument, questionnaire about the identity of participants and 20 items of related statements about students' beliefs in mathematics, as well as interview guides as supporting instruments. The statement in the questionnaire is divided into 10 positive statements and 10 negative statements related to mathematics. The results of this study showed that firstly, almost all students, both male, and female, have a decline of beliefs in mathematics learning at the junior high school level. Second, the factors that affect the decreasing level of students' belief in mathematics during the junior high school are the drastic changes in the subject that becomes more difficult and more formulas to be memorized, and many lessons do not use concrete objects. Further, the teachers' attitudes who are also very different from when they are in elementary school which are more comfortable, their social conditions are changed because they live in dorms that have many activities (must be followed) that makes them busy so that they are difficult to find free time to learn outside the school hours. Third, students' beliefs about mathematics learning have shifted from positive to negative or vice versa.